UV/UV step-curing of optically clear acrylate adhesives for mobile devices - J-S. Kim; G-S. Shim; D. Baek; J-H. Back; S-W. Jang; H-J. Kim; J-S. Choi; J-S. Yeom (eXPRESS Polymer Letters)
In order to overcome the issues of rework and height difference in the manufacturing of smart devices, UV/UV stepwise curing was conducted on acrylate-based optically clear adhesives. Photo differential scanning calorimetry was used to confirm the results of curing of samples that were processed both with and without acrylic acid, over a range of UV light exposure times for a primary curing process. The samples processed at 0.6 J/cm2 of UV energy with and without acrylic acid showed the highest amount of residual monomers after primary curing. The amount of residual monomers observed in primary-cured samples decreased as the amount of UV light energy increased, from 0.9 to 1.5 J/cm2. After secondary curing, only the samples cured at 0.6 J/cm2 showed small amounts of residual monomers, while the samples exposed to other UV energies showed very few residual monomers, implying that these samples were completely cured during the secondary curing step. Adhesion properties were evaluated using peel and tack tests, while the viscoelastic properties of the samples were confirmed by dynamic mechanical analysis. Our results indicate that uniform physical properties were achieved after secondary curing. The effects of stepwise curing are demonstrated by the difference in gel fractions determined after primary and secondary curing.